Promoting the use of local literacies in EFL pre-service teachers to inspire their teaching practice - Nieto Gómez, Yuly Andrea (Colombian Applied Linguistics Journal, 2018)
Involving teachers and students in an interaction with their community can provide opportunities to develop literacies from a critical viewpoint. From this perspective, an active exploration and transformation of socio cultural realities can be promoted. This article will serve as a reflection on the theory of community-based pedagogies as a means of fostering pre-service language teachers’ commitment in the construction of an alternative curriculum. Additionally, it calls for the appreciation of cultural context as a text for shaping and reconstructing the world, where learners explore their everyday understandings and practices, and teachers become authors of a curriculum that engages with material realities (Luke & Woods, 2009). Thus, it promotes inquiry in early teaching experiences as a source for creating new alternatives and functional understandings through problem posing involving diversity, creativity, and reflections as the main core in the curriculum (Short & Burke, 1991). Moreover, it supports valuing local knowledge (Canagarajah, 2005) as the foundation of an inclusive learning environment that empowers prospective teachers to envision their practice as an emancipatory exercise that demands relating the community to the classroom dynamic. Finally, it concludes that exploring socio cultural assets with the aim of enriching the EFL curriculum can inspire a context-sensitive practice that transforms both pre-service teachers and students’ lived experiences.